Fordyce happiness training program on the competence of mothers of premature infants admitted to the NICU from Middle East: A quasi-experimental study - Fereshteh Ghaljaei; Marie Hastings-Tolsma; Nasrin Rezaee (Pediatrics and Neonatology, 2023)
The purpose of this study was to determine the effect of the Fordyce Happiness Training Program on the parental competence of mothers of premature infants admitted to the neonatal intensive care unit (NICU). This quasi-experimental study was performed on 80 mothers of premature infants who were admitted to a NICU in Iran. Mean Parenting Sense of Competence Scale (PSOC) scores of participants in the intervention group before and after training were 61.32 ± 6.44 and 68.52 ± 2.52. Mean PSOC scores for those in the control group before and after the intervention were 64.47 ± 11.08 and 65.30 ± 6.90, respectively. The two groups showed significant differences in terms of parental competence after the happiness training program (p = 0.0001). NICU admission of a premature baby not only has a negative effect on the mother's emotional state but it can also adversely affect the parental sense of competence. Therefore, considering the psychological needs of mothers of premature infants, it is worth considering implementation of programs such as Fordyce Happiness Training, to promote and maintain the mental health of mothers.